Association between C-reactive protein levels and development of post-stroke depression: A systematic review and meta-analysis. Issue 4 (November 2022) - Jiang, Guizhen; Zhou, Dajin; Yan, Xiumei; Zheng, Qingbin; Tang, Zhuoqiong
Background and aims: Different prospective cohort studies have focused on the C-reactive protein ( ie, a pentameric protein) biomarker as a predictor of post-stroke depression. In this review and meta-analysis, we will attempt to synthesize the evidence for the association between C-reactive protein and the development of post-stroke depression. Methods: We systematically searched five academic databases for relevant studies according to the PRISMA guidelines. We evaluate the comparative levels of C-reactive protein in patients with stroke and/without depression, and analyzed the hazard ratio to evaluate the overall risk of C-reactive protein levels in patients with stroke. Results: We selected eligible studies with 2534 patients (mean age: 65.2 ± 5.9 years) from the initial 10 926 studies in the databases. Increased C-reactive protein levels (Hedge's g, 0.84) in patients with stroke and depression as compared to patients with stroke without depression. Increased levels of C-reactive protein were associated with the onset of depression (Hazard's ratio, 1.6) in patients with stroke. Conclusion: Our findings provide an association of C-reactive protein with the development of post-stroke depression, and present higher levels than patients with stroke without depression. Additionally, our findings support the role of C-reactive protein levels as markers for predicting depression in patients with stroke.